Genetic analysis and chromosome mapping of resistance to Fusarium oxysporum f. sp. niveum (FON) race 1 and race 2 in watermelon (Citrullus lanatus L.) - Ren, Yi; Di Jiao; Gong, Guoyi; Zhang, Haiying; Guo, Shaogui; Zhang, Jie; Xu, Yong (Molecular breeding, 2015)
Fusarium wilt (FW) caused by Fusarium oxysporum f. sp. niveum (FON) is the major soilborne disease of watermelon (Citrullus lanatus L.). The development and deployment of resistant cultivars is generally considered to be an effective approach to control FW. In this study, an F8 population consisting of 103 recombinant inbred lines derived from a cross between the cultivar 97103 and a wild accession PI 296341-FR was used for FON race 1 and race 2 fungal inoculations. One major QTL on chromosome 1 for FON race 1 resistance was detected with a logarithm of odds of 13.2 and explained phenotypic variation R ² = 48.1 %; two QTLs of FON race 2 resistance on chromosomes 9 and 10 were discovered based on the high-density integrated genetic map we constructed. The nearest molecular marker should be useful for marker-assisted selection of FON race 1 and race 2 resistance. One receptor kinase, one glucan endo-1,3-β-glucosidase precursors and three acidic chitinase located in the FON-1 QTL genomic region. In Qfon2.1 QTL region, one lipoxygenase gene, five receptor-like kinases and four glutathione S-transferase genes are discovered. One arginine biosynthesis bifunctional protein, two receptor kinase proteins and one lipid-transfer protein located in Qfon2.2 QTL region. Based on SNP analysis by using 20 re-sequenced accessions of watermelon and 231-plant F₂ population generated from Black Diamond × Calhoun Grey, we developed a SNP marker Chr1SNP_502124 for FON-1 detection.